Legal Uncertainty in Criminal Enforcement with the Use of Artificial Intelligence Technology in Indonesia - Ahmad Indarto, Bambang (International Journal of Law Social Sciences and Management, 2024)
Abstract. The use of Artificial Intelligence (AI) technology in law enforcement is amajor highlight in the context of information technology development in Indonesia.The impact of using AI raises various challenges that need to be addressedimmediately, such as difficulties in determining responsibility, privacy issues, and ethical implications. Even though several regulations already exist, the effectiveness of regulations in Indonesia in dealing with AI technology applications for criminal law enforcement still requires improvement. The urgency to update the law is becoming increasingly urgent, especially in accommodating developments in AI technology and overcoming emerging legal uncertainties. Comprehensive legal reform is needed to ensure that law enforcement using AI technology can be carried out effectively and by basic legal principles.